Agriculture and environment for developing regions - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Agriculture and environment for developing regions is the changed title of the former TROPAG journal Abstracts on tropical agriculture